EFFECTIVE WAYS TO SEPARATE FIBERS SUITABLE FOR SPINNING FROM WASTE MATERIAL - Mirzaakbarov, Azizbek; Muradov, Rustam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The high material and energy consumption of the analyzed fiber separation devices from fibrous waste and the uncertainty of fractionation reduce their efficiency, and the inability to separate fibers simultaneously makes it necessary to introduce additional technologies in some separation devices. This article studies the experiments and analyses conducted on the separation of short fibers included in the waste composition.